2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23409
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Instructional Methods Approach to Teaching a Circuits and Instrumentation Course

Abstract: The circuits and instrumentation course at James Madison University provides students with foundational knowledge in DC, transient, and AC circuit design and analysis. The 4-credit course is comprised of three weekly lectures and one weekly laboratory session. Given the breadth of content and desired level of technical analysis required of this junior level course offering, numerous methods for extending learning beyond the classroom and encouraging student engagement with the material have been explored. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Both studies report very positive impacts on student learning. Other studies which scored well in quality assessment - [6], [16], [17] -draw similar conclusions about the positive impact of active-learning in the classroom. Though active learning interventions vary between studies, there is consensus among high quality studies that active learning interventions improve student learning.…”
Section: Synthesis Of Best Practicessupporting
confidence: 62%
See 1 more Smart Citation
“…Both studies report very positive impacts on student learning. Other studies which scored well in quality assessment - [6], [16], [17] -draw similar conclusions about the positive impact of active-learning in the classroom. Though active learning interventions vary between studies, there is consensus among high quality studies that active learning interventions improve student learning.…”
Section: Synthesis Of Best Practicessupporting
confidence: 62%
“…. appears to provide a robust experience that complements a variety of learning styles" [16]. Another study similarly concluded that introducing a variety of experiences -such as guest lectures and field trips -into a course enhanced student learning [28].…”
Section: Synthesis Of Best Practicesmentioning
confidence: 99%